In vivo evaluation of osseointegration ability of sintered bionic trabecular porous titanium alloy as artificial hip prosthesis - Bai, Xiaowei; Li, Ji; Zhao, Zhidong; Wang, Qi; Lv, Ningyu; Wang, Yuxing; Gao, Huayi; Guo, Zheng; Li, Zhongli (Frontiers in Bioengineering and Biotechnology, 2022)
Hydroxyapatite (HA) coatings have been widely used for improving the bone-implant interface (BII) bonding of the artificial joint prostheses. However, the incidence of prosthetic revisions due to aseptic loosening remains high. Porous materials, including three-dimensional (3D) printing, can reduce the elastic modulus and improve osseointegration at the BII. In our previous study, we identified a porous material with a sintered bionic trabecular structure with in vitro and in vivo bio-safety as well as in vivo mechanical safety. This study aimed to compare the difference in osseointegration ability of the different porous materials and HA-coated titanium alloy in the BII. We fabricated sintered bionic trabecular porous titanium acetabular cups, 3D-printed porous titanium acetabular cups, and HA-coated titanium alloy acetabular cups for producing a hip prosthesis suitable for beagle dogs. Subsequently, the imaging and histomorphological analysis of the three materials under mechanical loading in animals was performed (at months 1, 3, and 6). The results suggested that both sintered bionic porous titanium alloy and 3D-printed titanium alloy exhibited superior performances in promoting osseointegration at the BII than the HA-coated titanium alloy. In particular, the sintered bionic porous titanium alloy exhibited a favorable bone ingrowth performance at an early stage (month 1). A comparison of the two porous titanium alloys suggested that the sintered bionic porous titanium alloys exhibit superior bone ingrowth properties and osseointegration ability. Overall, our findings provide an experimental basis for the clinical application of sintered bionic trabecular porous titanium alloys.